2014
DOI: 10.1186/1471-2318-14-81
|View full text |Cite
|
Sign up to set email alerts
|

Data sharing between home care professionals: a feasibility study using the RAI Home Care instrument

Abstract: BackgroundAcross Ontario, home care professionals collect standardized information on each client using the Resident Assessment for Home Care (RAI-HC). However, this information is not consistently shared with those professionals who provide services in the client’s home. In this pilot study, we examined the feasibility of sharing data, from the RAI-HC, between care coordinators and service providers.MethodsAll participants were involved in a one-day training session on the RAI-HC. The care coordinators shared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The interRAI home-care assessment is also used across Canada, Europe, some states in the United States, and the Asia-Pacific Rim (Hong Kong, Singapore, Japan, Australia, New Zealand; Morris et al, 2012;Salahudeen & Nishtala, 2019). Other research has demonstrated the feasibility and usefulness of sharing interRAI home-care assessments in improving interprofessional communication and potentially decreasing assessment duplication and workload (Guthrie et al, 2014). The absence of an integrated health record and supportive health information technology negatively influences system capacity to meet the needs of older adults with multiple chronic conditions (Grembowski et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The interRAI home-care assessment is also used across Canada, Europe, some states in the United States, and the Asia-Pacific Rim (Hong Kong, Singapore, Japan, Australia, New Zealand; Morris et al, 2012;Salahudeen & Nishtala, 2019). Other research has demonstrated the feasibility and usefulness of sharing interRAI home-care assessments in improving interprofessional communication and potentially decreasing assessment duplication and workload (Guthrie et al, 2014). The absence of an integrated health record and supportive health information technology negatively influences system capacity to meet the needs of older adults with multiple chronic conditions (Grembowski et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The Patient Falls Risk Report is a one-page report that was originally designed by the researchers of this study with knowledge from preliminary research and the Behaviour Change Wheel theoretical framework (Guthrie et al, 2014; Michie, Atkins, & West, 2014; Nova, Zarrin, & Heckman, 2020a, 2020b). It relays information derived from the interRAI-HC assessment about home care client falls risk, particularly if the client is at moderate or high risk of future falls.…”
Section: The Patient Falls Risk Reportmentioning
confidence: 99%
“…Recipients would then schedule an appointment with the patient to discuss their results, collect missing information, and develop a care plan, as would be expected in normal primary care practice. Since falls are highly preventable with timely screening and assessment, we believed that sharing the report with primary care providers in a usable, actionable, and context-appropriate manner could enhance falls-related care planning (Guthrie et al, 2014; Nova et al, 2020b; Stolee et al, 2010). The purpose of this study was to develop and test the usability of the Patient Falls Risk Report for sharing clinical information from home care to primary care in partnership with primary care providers.…”
Section: The Patient Falls Risk Reportmentioning
confidence: 99%
“…However, previous research has noted health care professionals' reluctance to change assessment practices to include standardized instruments and/or self-report tools, because of a preference and comfort with current practices (Giosa, Stolee, & Holyoke, 2021;Guthrie et al, 2014;Nova, Zarrin, & Heckman, 2020b). Therefore, the overall goal of this study was to implement the interRAI Check-Up into SGS care pathways to remotely assess older adults during the pandemic, and to evaluate the impact of the implementation.…”
Section: Introductionmentioning
confidence: 99%